Thermally conductive silicone composition
By using inorganic fillers with multiple particle size distributions and optimized formulas in thermally conductive silicone, the problems of overflow and filler separation during thermal expansion and shrinkage are solved, and high thermal conductivity and good electrical insulation and discharge performance are achieved.
Patent Information
- Application Number
- JP2024073852
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-20
- Filing Date
- 2024-04-30
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2044-04-30
AI Technical Summary
Existing thermally conductive silicone compositions are prone to overflow during thermal expansion and shrinkage, and the filler is separated from the base oil, resulting in insufficient thermal conductivity and reliability. At the same time, the thickness of the heat dissipation plate leads to limited thermal conductivity.
Inorganic fillers and silicone materials with a variety of particle size distributions are used to improve the thermal conductivity of thermally conductive silicone by adjusting the particle size distribution and combination of fillers, and ensure low layer thickness and good electrical insulation, discharge and heat dissipation performance through optimization of formulation and process.
The high thermal conductivity, low layer thickness, good electrical insulation and discharge performance of thermally conductive silicone are achieved, and the reliability and functionality of thermally conductive silicone are improved.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermally conductive silicone composition. [Background technology]
[0002] Recently, the demand for thermal management has increased with the increasing performance and miniaturization of electronic components such as power modules and CPUs. Thermally conductive grease and heat dissipation sheets are used for this thermal management. Thermally conductive grease has problems with pumping out, where the thermal expansion and contraction of the heating element and heat exchanger causes the grease to be pushed out from the application area, and with the filler and oil separating over time, and is still in the process of development in terms of reliability and functionality. On the other hand, heat dissipation sheets are molded products and do not have the above problems, but there are concerns about their heat dissipation performance in terms of thermal resistance and contact resistance that arise when the heat dissipation sheet itself becomes thicker.
[0003] To address this issue, a technique has been proposed in which a large particle size inorganic filler or multiple types of inorganic fillers are used to increase the thermal conductivity of a composition containing a thermally conductive filler and silicone. For example, Patent Document 1 discloses a thermally conductive polysiloxane composition that uses silicon carbide having at least two peaks in the particle size distribution. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-88685 A Summary of the Invention [Problem to be solved by the invention]
[0005] When considering thermal resistance, it is important for heat dissipation materials to be applied thinly. BLT (Bond-Line-Thickness) is an indicator of how thinly the material can be applied. The thickness of the heat dissipation material has a significant effect on heat dissipation, and making it thinner contributes to reducing thermal resistance, so BLT characteristics are important for high heat dissipation materials.
[0006] Furthermore, according to the findings of the inventors, it was found that there is room for improvement in the thermally conductive polysiloxane composition as described in Patent Document 1 in terms of electrical insulation properties, BLT properties, dischargeability, and heat dissipation properties.
[0007] An object of the present invention is to provide a thermally conductive silicone composition that has excellent electrical insulation properties, dischargeability, and heat dissipation properties, and also has a low BLT. [Means for solving the problem]
[0008] The present invention relates to the following [1] to [6]. [1] (A) a polyorganosiloxane having an alkenyl group bonded to a silicon atom; (B) a polyorganohydrogensiloxane having hydrogen atoms bonded to silicon atoms; (C) Platinum-based catalyst; (D) the following general formula (1): [ka] [During the ceremony, R 1 A group having an alkoxysilyl group having 1 to 4 carbon atoms R 2 The following general formula (2): [ka] (In the formula, R 4 are each independently a monovalent hydrocarbon group having 1 to 12 carbon atoms, and Y is R 4and aliphatic unsaturated groups, and d is an integer of 2 to 60. X: each independently a divalent hydrocarbon group having 2 to 10 carbon atoms a and b: each independently an integer of 1 or more c: An integer greater than or equal to 0 a+b+c: an integer greater than or equal to 4 R 3 each independently represents a monovalent hydrocarbon group having 1 to 6 carbon atoms or a hydrogen atom. A siloxane compound represented by the formula: (E) a thermally conductive filler; A thermally conductive silicone composition comprising: The component (A) contains (A-1) a polyorganosiloxane having two or more alkenyl groups bonded to silicon atoms in the molecule, The (B) component contains (B-1) a polyorganohydrogensiloxane having two or more hydrogen atoms bonded to silicon atoms in the molecule, The component (E) is (E-1) Silicon carbide having a particle size distribution peak in the range of 10 μm to 40 μm; (E-2) a first thermally conductive filler having a thermal conductivity of 10 W / mK to 300 W / mK and a particle size distribution peak in the range of 0.1 μm or more and 1.0 μm or less; (E-3) a second thermally conductive filler having a thermal conductivity of 10 W / mK to 300 W / mK and a particle size distribution peak in the range of more than 1.0 μm and less than 10 μm; and (E-4) A third thermally conductive filler (excluding silicon carbide) having a thermal conductivity of 60 W / mK to 300 W / mK and a particle size distribution peak in the range of 10 μm to 40 μm, the total content of components (A), (B), and (D) is 1.0 to 10.0 parts by mass per 100 parts by mass of component (E); and A thermally conductive silicone composition, in which the amount of component (E-2) is no more than 28.0 parts by mass per 100 parts by mass of component (E). [2] The component (E-2) is at least one selected from the group consisting of alumina, aluminum nitride, aluminum hydroxide, magnesium oxide, zinc oxide, crystalline silica, aluminum, boron nitride, and graphitized carbon, The component (E-3) is at least one selected from the group consisting of alumina, aluminum nitride, aluminum hydroxide, magnesium oxide, zinc oxide, crystalline silica, aluminum, boron nitride, and graphitized carbon, and The thermally conductive silicone composition according to [1], wherein the component (E-4) is one or more members selected from the group consisting of aluminum nitride, boron nitride, and graphitized carbon. [3] The thermally conductive silicone composition according to [1] or [2], further comprising at least one member selected from the group consisting of (A-2) polyorganosiloxanes having one alkenyl group bonded to a silicon atom in the molecule, and (B-2) polyorganohydrogensiloxanes having one hydrogen atom bonded to a silicon atom in the molecule. [4] For 100 parts by mass of component (E), The content of the component (E-1) is 5.0 to 30.0 parts by mass, The content of the component (E-2) is 10.0 to 28.0 parts by mass, The content of the component (E-3) is 15.0 to 40.0 parts by mass, and The content of the component (E-4) is 5.0 to 40.0 parts by mass. The thermally conductive silicone composition according to any one of [1] to [3]. [5] A cured product obtained by curing the thermally conductive silicone composition according to any one of [1] to [4]. [6] An electronic part comprising the thermally conductive silicone composition according to any one of [1] to [4]. Effect of the Invention
[0009] The present invention provides a thermally conductive silicone composition that has excellent electrical insulation properties, dischargeability, and heat dissipation properties, and also has a low BLT. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [Terminology definition] The structural units of siloxane compounds are sometimes described by the following abbreviations (hereinafter, these structural units are referred to as "M units" and "D units" respectively). H (sometimes called "units"). M :Si(CH3)3O 1 / 2 M H :SiH(CH3)2O 1 / 2 M Vi :(CH=CH2)(CH3)2SiO 1 / 2 D :Si(CH3)2O 2 / 2 D H :SiH(CH3)O 2 / 2
[0011] In this specification, specific examples of groups are as follows. Examples of the monovalent hydrocarbon group include an alkyl group, a cycloalkyl group, an aryl group, an aralkyl group, and an alkenyl group. Examples of the monovalent hydrocarbon group having no aliphatic unsaturated bond include the above-mentioned monovalent hydrocarbon groups other than an alkenyl group. The alkenyl group is a straight-chain or branched group having 2 to 6 carbon atoms, and examples thereof include a vinyl group, an allyl group, a 3-butenyl group, and a 5-hexenyl group. The alkyl group is a straight-chain or branched group having 1 to 18 carbon atoms, and examples thereof include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, an octyl group, a decyl group, a dodecyl group, a hexadecyl group, and an octadecyl group. The cycloalkyl group is a monocyclic or polycyclic group having 3 to 20 carbon atoms, and examples thereof include a cyclopentyl group and a cyclohexyl group. The aryl group is an aromatic group containing a monocyclic or polycyclic group having 6 to 20 carbon atoms, and examples thereof include a phenyl group and a naphthyl group. The aralkyl group is an alkyl group substituted with an aryl group, and examples thereof include a 2-phenylethyl group and a 2-phenylpropyl group. The alkylene group is a straight-chain or branched group having 1 to 18 carbon atoms, and examples thereof include a methylene group, an ethylene group, a trimethylene group, a 2-methylethylene group, and a tetramethylene group. The alkenyl group, the alkyl group, the cycloalkyl group, the aryl group, the aralkyl group and the alkylene group may be substituted with a halogen such as chlorine, fluorine or bromine, a cyano group, etc. Examples of the group substituted with a halogen include a chloromethyl group, a chlorophenyl group, a 3,3,3-trifluoropropyl group, etc., and examples of the group substituted with a cyano group include a 2-cyanoethyl group, etc.
[0012] In this specification, "(A) polyorganosiloxane having an alkenyl group bonded to a silicon atom" is also referred to as "component (A)". The same applies to "(C) platinum-based catalyst" and the like.
[0013] [Thermal conductive silicone composition] The thermally conductive silicone composition (hereinafter also simply referred to as "composition") comprises the following: (A) a polyorganosiloxane having an alkenyl group bonded to a silicon atom; (B) a polyorganohydrogensiloxane having hydrogen atoms bonded to silicon atoms; (C) Platinum-based catalyst; (D) the following general formula (1): [ka] [During the ceremony, R 1 A group having an alkoxysilyl group having 1 to 4 carbon atoms R 2 The following general formula (2): [ka] (In the formula, R 4 are each independently a monovalent hydrocarbon group having 1 to 12 carbon atoms, and Y is R 4 and aliphatic unsaturated groups, and d is an integer of 2 to 60. X: each independently a divalent hydrocarbon group having 2 to 10 carbon atoms a and b: each independently an integer of 1 or more c: An integer greater than or equal to 0 a+b+c: an integer greater than or equal to 4 R 3 each independently represents a monovalent hydrocarbon group having 1 to 6 carbon atoms or a hydrogen atom. A siloxane compound represented by the formula: (E) a thermally conductive filler; A thermally conductive silicone composition comprising: The component (A) contains (A-1) a polyorganosiloxane having two or more alkenyl groups bonded to silicon atoms in the molecule, The (B) component contains (B-1) a polyorganohydrogensiloxane having two or more hydrogen atoms bonded to silicon atoms in the molecule, The component (E) is (E-1) Silicon carbide having a particle size distribution peak in the range of 10 μm to 40 μm; (E-2) a first thermally conductive filler having a thermal conductivity of 10 W / mK to 300 W / mK and a particle size distribution peak in the range of 0.1 μm or more and 1.0 μm or less; (E-3) a second thermally conductive filler having a thermal conductivity of 10 W / mK to 300 W / mK and a particle size distribution peak in the range of more than 1.0 μm and less than 10 μm; and (E-4) A third thermally conductive filler (excluding silicon carbide) having a thermal conductivity of 60 W / mK to 300 W / mK and a particle size distribution peak in the range of 10 μm to 40 μm, the total content of components (A), (B), and (D) is 1.0 to 10.0 parts by mass per 100 parts by mass of component (E); and The amount of the component (E-2) is not more than 28.0 parts by mass per 100 parts by mass of the component (E).
[0014] <(A) Polyorganosiloxane having an alkenyl group bonded to a silicon atom> (A) polyorganosiloxane having an alkenyl group bonded to a silicon atom is a component that serves as a base polymer in the composition. Component (A) includes (A-1) a polyorganosiloxane having two or more alkenyl groups bonded to a silicon atom in the molecule.
[0015] <(A-1) Polyorganosiloxane having two or more silicon-bonded alkenyl groups in the molecule> Component (A-1) is a polyorganosiloxane having two or more alkenyl groups bonded to silicon atoms in the molecule. An addition reaction between the alkenyl groups of component (A-1) and the hydrosilyl groups (Si-H groups) of component (B-1) forms a network structure in the cured product of the composition.
[0016] The component (A-1) is not particularly limited as long as it can form the network structure together with the component (B-1). The component (A-1) is typically represented by the general formula (I): (R 11 ) a1 (R 12 ) b1 SiO (4-a1-b1) / 2 (I) (In the formula, R 11 is an alkenyl group; R 12 is a monovalent hydrocarbon group having no aliphatic unsaturated bonds; a1 is an integer of 1 to 3; b1 is an integer from 0 to 2, provided that a1+b1 is an integer from 1 to 3. The number of alkenyl groups bonded to silicon atoms in the component (A-1) is preferably 2 to 100, and more preferably 2 to 50, per molecule.
[0017] R 11 R is preferably a vinyl group from the viewpoints of ease of synthesis and of not impairing the fluidity of the composition before curing or the heat resistance of the composition after curing. a is preferably 1 from the viewpoint of ease of synthesis. 12is preferably a methyl group or a phenyl group, and particularly preferably a methyl group, from the viewpoints of ease of synthesis and an excellent balance of properties such as mechanical strength and fluidity before curing.
[0018] The organic group bonded to the silicon atom of the other siloxane unit in the component (A-1) is, for example, a monovalent hydrocarbon group that does not have an aliphatic unsaturated bond. 12 For the same reasons as above, a methyl group or a phenyl group is preferred, and a methyl group is particularly preferred.
[0019] R 11 may be present either at the terminal or intermediate of the molecular chain of component (A-1), or may be present at both.
[0020] The siloxane skeleton of the component (A-1) can be linear or branched, that is, the component (A-1) can be a linear polyorganosiloxane (A-1-1) or a branched polyorganosiloxane (A-1-2).
[0021] (A-1-1) As the linear polyorganosiloxane, both ends are RSiO 1 / 2 Blocked in units, intermediate unit is R 2 2SiO 2 / 2 A linear polyorganosiloxane consisting of only units (where R is R 11 or R 12 and R 11 is an alkenyl group, R 12 is a monovalent hydrocarbon group that does not have an aliphatic unsaturated bond and has two or more R 11 (Containing RSiO in component (A1-1) 1 / 2 The unit is R. 11 R 12 2SiO 1 / 2 Units, R 11 2R 12 SiO 1 / 2 Unit or R 11 3SiO 1 / 2 The unit is preferably R 11 R 122SiO 1 / 2 It is particularly preferred that the unit is a unit.
[0022] The component (A-1) has R at both ends. 11 R 12 2SiO 1 / 2 Blocked in units, intermediate unit is R 12 2SiO 2 / 2 It is more preferable that the component (A1-1) is a linear polyorganosiloxane consisting only of M units. vi D n M vi A linear polyorganosiloxane represented by the formula (i.e., both ends are M vi It is particularly preferred that the polyorganosiloxane is a linear polyorganosiloxane in which the intermediate unit is only a D unit (dimethylsiloxane unit) and the intermediate unit is only a D unit (dimethylsiloxane unit). n " means that the intermediate unit consists only of D units, and here "n" means the degree of polymerization of the D units, and is a value that changes depending on the viscosity of the polyorganosiloxane in question.
[0023] (A-1-2) Branched polyorganosiloxane has SiO as an essential unit. 4 / 2 Units and RSiO 1 / 2 Including units, as well as RSiO as an arbitrary unit 2 / 2 Units and / or RSiO 3 / 2 In particular, the branched polyorganosiloxanes include those containing the units R 11 or R 12 However, in R, there are two or more R per molecule. 11 In order to act as crosslinking points in the curing reaction, at least three R per molecule are R 11 and the remainder is R 12 From the viewpoint of providing a cured product of the composition with excellent mechanical strength, it is preferable that the cured product is RSiO 1 / 2 Units and SiO 4 / 2 The molar ratio of the units is preferably within the range of 1:0.8 to 1:3, and the resin is a solid or viscous semi-solid resin at room temperature.
[0024] In the component (A-1-2), R 11 is R3SiO 1 / 2 It may also exist as a unit R, RSiO unit or RSiO 3 / 2 It may also exist as the unit R. From the viewpoint of obtaining fast curing at room temperature, RSiO 1 / 2 Some or all of the units are R 11 R 12 2SiO 1 / 2 It is preferable that the unit is a unit.
[0025] <Component (A) other than component (A-1)> The (A) component may contain a component (A) other than the (A-1) component (hereinafter also referred to as the (A-2) component). The (A-2) component may be a polyorganosiloxane having one alkenyl group bonded to a silicon atom in the molecule. The siloxane skeleton of the (A-2) component, including preferred embodiments, is as described above for the (A-1) component.
[0026] The component (A-2) is preferably a linear polyorganosiloxane having one alkenyl group bonded to a silicon atom in the molecule. 11 R 12 2SiO 1 / 2 unit and the other end is R 12 3SiO 1 / 2 Blocked in units, intermediate unit is R 12 2SiO 2 / 2 It is more preferable that the component (A-2) is a linear polyorganosiloxane consisting of only M units. vi D n A linear polyorganosiloxane represented by M is particularly preferred.
[0027] <Preferred embodiments of component (A)> The viscosity of component (A) is preferably 0.01 to 500 Pa·s at 23°C, more preferably 0.05 to 300 Pa·s, and particularly preferably 0.1 to 100 Pa·s. When the viscosity of component (A) is within the above range, the filler and the polymer can be easily kneaded in the production process, and the final product can have excellent electrical insulation properties, BLT properties, dischargeability, and heat dissipation properties. In addition, when the viscosity of component (A) is 0.01 Pa·s or more at 23°C, the volatilization of low molecular weight components in the production process is suppressed, and the properties of the thermally conductive silicone composition can be efficiently satisfied. On the other hand, when the viscosity of component (A) is 500 Pa·s or less at 23°C, component (E) and the polymer components (component (A) and component (B)) tend to be combined. Here, when component (A) is a combination of two or more types, the viscosity of component (A) means the viscosity of the mixed alkenyl group-containing polyorganosiloxane. In this specification, the viscosity is a value measured in accordance with JIS K 6249 using a rotational viscometer with appropriately set spindle number and rotation speed at 23°C.
[0028] The component (A) may be one type of component or a combination of two or more types of components. For example, the component (A) may consist of only two or more types of the (A-1) component, or may be a mixture of one or more types of the (A-1) component and one or more types of the (A-2) component.
[0029] <(B) Polyorganohydrogensiloxane having hydrogen atoms bonded to silicon atoms> (B) Polyorganohydrogensiloxane having hydrogen atoms bonded to silicon atoms includes (B-1) polyorganohydrogensiloxane having two or more hydrogen atoms bonded to silicon atoms in the molecule. The component (B) is not particularly limited as long as it can form the above-mentioned network structure together with the component (A).
[0030] <(B-1) Polyorganohydrogensiloxane having two or more hydrogen atoms bonded to silicon atoms in the molecule> The component (B-1) functions as a crosslinking agent for the component (A). The component (B-1) is typically represented by the general formula (II): (R 13 ) c H d SiO (4-c1-d1) / 2 (II) (In the formula, R 13 represents a monovalent hydrocarbon group having no aliphatic unsaturated bonds; c1 is an integer from 0 to 2; d1 is an integer from 1 to 3, provided that c1+d1 is an integer from 1 to 3. The molecule has two or more units represented by the following formula:
[0031] R 13 is preferably a methyl group from the viewpoint of ease of synthesis, and d1 is preferably 1 from the viewpoint of ease of synthesis.
[0032] From the viewpoint of ease of synthesis, it is preferable that the (B-1) component has 3 or more siloxane units. In addition, from the viewpoints of not volatilizing even when heated to a curing temperature, and of having excellent fluidity and being easily mixed with the (A) component, the number of siloxane units in the (B-1) component is preferably 6 to 200, and particularly preferably 10 to 150. From the viewpoint of efficiently functioning as a crosslinking agent for the (A) component, it is preferable that the (B-1) component has 3 or more units represented by general formula (II) in the molecule.
[0033] The siloxane skeleton in component (B-1) may be linear, branched, or cyclic, with linear being preferred. In the case of component (B-1), the hydrogen atoms bonded to the silicon atoms may be present at the terminals or in the middle units, but are preferably present in the middle units.
[0034] The component (B-1) is a compound (B-1-1) in which both ends are independently represented by R 14 3SiO 1 / 2 It is blocked by units, and the intermediate unit is R 14 2SiO 2 / 2A linear polyorganohydrogensiloxane consisting of only units, and (B-1-2)R 14 3SiO 1 / 2 Units and SiO 4 / 2 Polyorganohydrogensiloxane (in each of the above formulas, R 14 are each independently a hydrogen atom or a monovalent hydrocarbon group having no aliphatic unsaturated bonds, provided that R 14 At least three of these are hydrogen atoms.
[0035] In the case of components (B-1-1) and (B-1-2), R 14 3SiO 1 / 2 The unit is HR. 15 2SiO 1 / 2 Units and R 15 3SiO 1 / 2 The units are listed as R 14 2SiO 2 / 2 The unit is HR. 15 SiO 2 / 2 Units and R 15 2SiO 2 / 2 Units (in the above formulas, R 15 is a monovalent hydrocarbon group having no aliphatic unsaturated bonds).
[0036] The (B-1) component has M at both ends. H The intermediate units are D units (dimethylsiloxane units) and D H A linear polyorganohydrogensiloxane consisting only of units (dimethylsiloxane units), and H It is particularly preferred that the polyorganohydrogensiloxane is a linear polyorganohydrogensiloxane in which the intermediate units are solely composed of D units (dimethylsiloxane units).
[0037] <Polyorganohydrogensiloxane other than component (B-1)> The (B) component may contain a (B) component other than the (B-1) component (hereinafter also referred to as the (B-2) component). The (B-2) component may be a polyorganohydrogensiloxane having one hydrogen atom bonded to a silicon atom in the molecule. The siloxane skeleton in the (B-2) component may be linear, branched or cyclic, and is preferably linear. In the (B-2) component, the hydrogen atom bonded to the silicon atom may be present at the terminal or in the intermediate unit.
[0038] The component (B-2) is M H D n A linear polyorganohydrogensiloxane represented by M is particularly preferred.
[0039] <Preferred Embodiments of Component (B)> The viscosity of component (B) at 23°C is preferably 0.01 to 500 mPa·s, more preferably 1 to 300 mPa·s, and particularly preferably 5 to 100 mPa·s. When the viscosity of component (B) is within the above range, component (E) and the polymer components (components (A) and (B)) can be easily kneaded together in the production process, resulting in a composition with better electrical insulation properties, BLT properties, dischargeability, and heat dissipation properties. The viscosity is as described above for component (A).
[0040] The component (B) may be one type of component or a combination of two or more types of components. For example, the component (B) may consist of only two or more types of the (B-1) component, or may be a mixture of one or more types of the (B-1) component and one or more types of the (B-2) component.
[0041] <Preferred embodiments of component (A) and component (B)> From the standpoints of curability and heat resistance, as well as controlling the hardness of the material, it is preferable that the thermally conductive silicone composition further contains one or more members selected from the group consisting of (A-2) polyorganosiloxanes having one alkenyl group bonded to a silicon atom in the molecule, and (B-2) polyorganohydrogensiloxanes having one hydrogen atom bonded to a silicon atom in the molecule.
[0042] <(C) Platinum-based catalyst> (C) The platinum catalyst is a catalyst for promoting the addition reaction between the alkenyl groups in component (A) and the hydrosilyl groups in component (B).
[0043] Examples of the (C) component include platinum compounds such as chloroplatinic acid, reaction products of chloroplatinic acid and alcohol, platinum-olefin complexes, platinum-vinylsiloxane complexes, platinum-ketone complexes, and platinum-phosphine complexes. Among these, platinum-vinylsiloxane complexes are preferred because of their good catalytic activity, and Karstedt complexes, platinum-1,1,3,3-tetramethyl-1,3-divinyldisiloxane complexes (platinum-methylvinylsiloxane dimer complexes), Ashley complexes, and platinum-2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane complexes (platinum-methylvinylsiloxane tetramer complexes) are particularly preferred because they cure in a short time at room temperature. The component (C) may be one type of component or a combination of two or more types of components.
[0044] <(D) Siloxane compound represented by general formula (1)> The component (D) is represented by the following general formula (1): [ka] [During the ceremony, R 1 A group having an alkoxysilyl group having 1 to 4 carbon atoms R 2 The following general formula (2): [ka] (In the formula, R 4 are each independently a monovalent hydrocarbon group having 1 to 12 carbon atoms, and Y is R 4 and aliphatic unsaturated groups, and d is an integer of 2 to 60. X: each independently a divalent hydrocarbon group having 2 to 10 carbon atoms a and b: each independently an integer of 1 or more c: An integer greater than or equal to 0 a+b+c: an integer greater than or equal to 4 R 3 each independently represents a monovalent hydrocarbon group having 1 to 6 carbon atoms or a hydrogen atom. As shown in the figure.
[0045] In the (D) component, R 1 Units including R 2 Units including SiR 3 The units represented by 2O do not necessarily have to be arranged as shown in the above general formula (1). For example, 1 Units including R 2 Between units containing SiR 3 Units represented by 2O may be present.
[0046] The siloxane compound having a cyclic structure represented by the general formula (1) can introduce many hydrolyzable groups into the cyclic structure, and since the hydrolyzable groups are concentrated in position, it is considered that the processing efficiency of the (E) component is high and higher loading is possible. In addition, since the heat resistance of the siloxane compound itself is high, it can impart high heat resistance to the thermally conductive silicone composition. In addition, the siloxane compound represented by the general formula (1) has the advantage that it can be easily obtained by addition reaction of, for example, a cyclic siloxane containing a hydrogen group, a siloxane having a vinyl group at one end, or a silane compound containing a vinyl group and a hydrolyzable group.
[0047] R 1 R is a group having an alkoxysilyl group having 1 to 4 carbon atoms, and is a hydrolyzable functional group.1 R may be bonded directly to X through silicon, or through a linking group such as an ester bond. 1 is preferably a group having the following structure: [ka]
[0048] R 1 is preferably a group having a structure having two or more alkoxysilyl groups, particularly three alkoxysilyl groups, since this tends to further improve the processing efficiency of the thermally conductive filler. 1 Preferably, contains a methoxysilyl group.
[0049] R 2 R is a linear organosiloxy group represented by the general formula (2). In the general formula (2), the number d is an integer of 2 to 60. When the number d is 2 to 60, the effect on fluidity is improved, high compounding is possible, and the viscosity of the siloxane compound itself can be suppressed. 4 are each independently a monovalent hydrocarbon group having 1 to 12 carbon atoms, and are linear or branched C 1-12 Examples of the hydrocarbon group include alkyl groups, and aryl groups such as phenyl and naphthyl. The hydrocarbon group may be substituted with halogen such as chlorine, fluorine, or bromine, and examples of such groups include perfluoroalkyl groups such as trifluoromethyl. R 4 is preferably a methyl group. 1 , R 4 and an aliphatic unsaturated group. The aliphatic unsaturated group preferably has 2 to 10 carbon atoms, more preferably 2 to 6 carbon atoms. In addition, the aliphatic unsaturated group preferably has a double bond at the end, since this facilitates the curing reaction. Y is preferably a methyl group or a vinyl group, since synthesis is easy.
[0050] R 1 and R 2is bonded to the cyclic siloxane portion of the siloxane represented by general formula (1) via the group X. The group X is a divalent hydrocarbon group having 2 to 10 carbon atoms, and examples thereof include alkylene groups such as -CH2CH2-, -CH2CH2CH2-, -CH2CH2CH2CH2CH2CH2-, -CH2CH(CH3)-, and -CH2CH(CH3)CH2-. From the viewpoint of ease of synthesis, it is preferable that X is -CH2CH2- or -CH2CH(CH3)-.
[0051] R 3 are each independently a monovalent hydrocarbon group having 1 to 6 carbon atoms or a hydrogen atom. 3 may be the same or different. R 3 is preferably a methyl group or a hydrogen atom.
[0052] a is an integer of 1 or more, and preferably 1. b is an integer of 1 or more, and preferably 1 or 2. c is an integer of 0 or more, and preferably 0 to 2. In addition, the sum of a+b+c is an integer of 4 or more, and is preferably 4 in terms of ease of synthesis.
[0053] Specific examples of the siloxane compound include compounds represented by the following structural formulas. [ka]
[0054] [ka]
[0055] Component (D) may be one type of component or a combination of two or more types of components.
[0056] <(E) Thermally conductive filler> (E) The thermally conductive filler is selected from the group consisting of: (E-1) Silicon carbide having a particle size distribution peak in the range of 10 μm to 40 μm; (E-2) a first thermally conductive filler having a thermal conductivity of 10 W / mK to 300 W / mK and a particle size distribution peak in the range of 0.1 μm or more and 1.0 μm or less; (E-3) a second thermally conductive filler having a thermal conductivity of 10 W / mK to 300 W / mK and a particle size distribution peak in the range of more than 1.0 μm and less than 10 μm; and (E-4) A third thermally conductive filler (excluding silicon carbide) having a thermal conductivity of 60 W / mK to 300 W / mK and a peak of the particle size distribution in the range of 10 μm or more and 40 μm or less is included.
[0057] <(E-1) Silicon carbide having a particle size distribution peak in the range of 10 μm or more and 40 μm or less> The (E-1) component is silicon carbide having a particle size distribution peak in the range of 10 μm to 40 μm. The silicon carbide is not particularly limited as long as it is of a grade that can be used as a thermally conductive filler, and commercially available products can be used. Examples of commercially available silicon carbide products include black silicon carbide and green silicon carbide manufactured by Pacific Random Co., Ltd. In addition, these silicon carbides that have been ultrafinely powdered can also be used.
[0058] When the (E-1) component has a monodisperse particle size distribution, the peak of the particle size distribution of silicon carbide is synonymous with the average particle size. The average particle size can be determined as a weight average value (or median size) or the like using a particle size distribution measuring device using, for example, a laser light diffraction method.
[0059] The (E-1) component preferably has a monodisperse particle size distribution. The thermally conductive (E-1) component preferably has a particle size distribution peak in the range of 15 μm to 35 μm, and particularly preferably has a particle size distribution peak in the range of 20 μm to 30 μm. From the viewpoints of electrical insulation properties, BLT properties, ejection properties, and heat dissipation properties, the BET specific surface area of the (E-1) component is preferably 0.01 to 5.0 m. 2 / g, and 0.5 to 3.0 m 2 / g is particularly preferred. The component (E-1) may be one type of component, or a combination of two or more types of components.
[0060] Silicon carbide can be used as the (E-2) component and / or the (E-3) component described later. When silicon carbide is used as the (E-2) component and / or the (E-3) component, the silicon carbide contained in the composition can have at least two peaks in the particle size distribution, i.e., a polydisperse particle size distribution. That is, the thermally conductive silicone composition can contain silicon carbide having a particle size distribution peak in the range of 10 μm to 40 μm as the (E-1) component, and silicon carbide having a particle size distribution peak in the range of 0.1 μm to 1.0 μm as the (E-2) component, and / or silicon carbide having a particle size distribution peak in the range of more than 1.0 μm to less than 10 μm as the (E-3) component.
[0061] <<(E-2) A first thermally conductive filler having a thermal conductivity of 10 W / mK to 300 W / mK and a particle size distribution peak in the range of 0.1 μm or more and 1.0 μm or less>> The thermal conductivity of the component (E-2) is a value measured by a laser flash method, and the peak of the particle size distribution is as described above for the component (E-1). The component (E-2) is not particularly limited and can be appropriately selected from known components. The component (E-2) is preferably alumina (thermal conductivity: 30 W / mK), aluminum nitride (thermal conductivity: 180 W / mK), aluminum hydroxide (thermal conductivity: 11 W / mK), magnesium oxide (thermal conductivity: 60 W / mK), zinc oxide (thermal conductivity: 25 W / mK), crystalline silica (thermal conductivity: 10 W / mK), aluminum (thermal conductivity: 250 W / mK), boron nitride (thermal conductivity: 60 to 200 W / mK), and graphitized carbon (thermal conductivity: 100 to 250 W / mK). From the viewpoints of electrical insulation properties, BLT properties, dischargeability, and heat dissipation, the BET specific surface area of the component (E-2) is 0.01 to 5 m 2 / g, and 0.1 to 1m 2 It is particularly preferred that the molecular weight is / g. The component (E-2) may be one type of component or a combination of two or more types of components.
[0062] <<(E-3) A second thermally conductive filler having a thermal conductivity of 10 W / mK to 300 W / mK and a particle size distribution peak in the range of more than 1.0 μm and less than 10 μm>> The thermal conductivity of the component (E-3) is as described above for the component (E-2), and the peak of the particle size distribution is as described above for the component (E-1).
[0063] The component (E-3) is not particularly limited and can be appropriately selected from known components. The component (E-3) is preferably alumina, aluminum nitride, aluminum hydroxide, magnesium oxide, zinc oxide, crystalline silica, aluminum, boron nitride, or graphitized carbon. From the viewpoints of electrical insulation properties, BLT properties, dischargeability, and heat dissipation, the BET specific surface area of the component (E-3) is 0.1 to 3.0 m 2 / g, and 0.5 to 2.0 m 2 It is particularly preferred that the molecular weight is / g. The component (E-3) may be one type of component or a combination of two or more types of components.
[0064] <(E-4) A third thermally conductive filler (excluding silicon carbide) having a thermal conductivity of 60 W / mK to 300 W / mK and a particle size distribution peak in the range of 10 μm to 40 μm> The thermal conductivity of the component (E-4) is as described above for the component (E-2), and the peak of the particle size distribution is as described above for the component (E-1).
[0065] The component (E-4) is not particularly limited and can be appropriately selected from known components. The component (E-4) is preferably aluminum nitride, boron nitride, or graphitized carbon. From the viewpoints of electrical insulation properties, BLT properties, dischargeability, and heat dissipation, the BET specific surface area of the component (E-4) is preferably 0.01 to 1.0 m 2 / g, and 0.1 to 0.5m 2 It is particularly preferred that the molecular weight is / g. The component (E-4) may be one type of component or a combination of two or more types of components.
[0066] <(E-5) Other thermally conductive fillers> The component (E) may contain, in addition to the components (E-1) to (E-4), (E-5) another thermally conductive filler.
[0067] Examples of the component (E-5) include thermally conductive fillers (e.g., silicon carbide, aluminum nitride) having a thermal conductivity of 10 W / mK to 300 W / mK and a particle size distribution peak in the range of more than 40 μm; and thermally conductive fillers having a thermal conductivity of 10 W / mK or more but less than 60 W / mK and a particle size distribution peak in the range of 10 μm or more and 40 μm or less. From the viewpoints of electrical insulation properties, BLT properties, dischargeability, and heat dissipation, the BET specific surface area of the component (E-5) is 0.1 to 3.0 m. 2 / g, and 0.5 to 2.0 m 2 It is particularly preferred that the molecular weight is / g.
[0068] The component (E-5) may be one type or a combination of two or more types.
[0069] <(F) Further Ingredients> The composition may contain further components (F) such as a reaction inhibitor, an organic solvent, an adhesion imparting agent, an inorganic pigment, an organic pigment, a thixotropy imparting agent, a viscosity modifier, an ultraviolet protection agent, an antifungal agent, a heat resistance improving agent, a flame retardant, etc. Each of the components (F) may be one type or a combination of two or more types.
[0070] <<Reaction inhibitors>> Examples of the reaction inhibitor include organic compounds having a polar group in the molecule, such as diallyl maleate, and organic compounds having an unsaturated bond, such as acetylene alcohols and their derivatives. The reaction inhibitor suppresses the curing reaction rate of the composition, and contributes to improving the balance between the workability of handling and the expression of adhesiveness and the curing rate.
[0071] <<Organic solvents>> The organic solvent is a component capable of dissolving or dispersing the components contained in the composition. Examples of the organic solvent include aromatic organic solvents such as toluene and xylene.
[0072] <<Other (F) Further Ingredients>> Component (F), other than the reaction inhibitor and organic solvent, can be appropriately selected from components used in thermally conductive silicone compositions.
[0073] [Content] The content of each component in the thermally conductive silicone composition is as follows: The total content of the (A) to (D) components is 1.0 to 10.0 parts by mass relative to 100 parts by mass of the (E) component. When the total content of the (A) to (D) components is less than 1.0 part by mass relative to 100 parts by mass of the (E) component, the thermal conductivity tends to be high, but the amount of polymer is very small relative to the (E) component, and there is a concern that the paste will not be formed. When the total content of the (A) to (D) components is more than 10.0 parts by mass relative to 100 parts by mass of the (E) component, the dischargeability is good, but the thermal conductivity is low. The total content of the (A) to (D) components is preferably 2.0 to 8.0 parts by mass, and particularly preferably 3.0 to 7.0 parts by mass relative to 100 parts by mass of the (E) component. In addition, the total content of the (A) to (D) components may be 6.0 to 8.0 parts by mass relative to 100 parts by mass of the (E) component.
[0074] The content of the (E-2) component is 28.0 parts by mass or less per 100 parts by mass of the (E) component. If the content of the (E-2) component exceeds 28.0 parts by mass per 100 parts by mass of the (E) component, the composition will not hold together. From the viewpoints of electrical insulation properties, BLT properties, dischargeability, and heat dissipation properties, the content of the (E-2) component is preferably 10.0 to 28.0 parts by mass, and particularly preferably 15.0 to 25.0 parts by mass per 100 parts by mass of the (E) component.
[0075] [Preferable content] The content of each component in the thermally conductive silicone composition is preferably as follows.
[0076] From the viewpoints of electrical insulation properties, BLT properties, ejection properties, and heat dissipation properties, the content of the (E-1) component per 100 parts by mass of the (E) component is preferably 5.0 to 30.0 parts by mass, more preferably 10.0 to 30.0 parts by mass, and particularly preferably 10.0 to 25.0 parts by mass.
[0077] From the viewpoints of electrical insulation properties, BLT properties, ejection properties, and heat dissipation properties, the content of the (E-3) component per 100 parts by mass of the (E) component is preferably 15.0 to 40.0 parts by mass, and particularly preferably 20.0 to 35.0 parts by mass.
[0078] From the viewpoints of electrical insulation properties, BLT properties, ejection properties, and heat dissipation properties, the content of the (E-4) component per 100 parts by mass of the (E) component is preferably 5.0 to 40.0 parts by mass, and particularly preferably 20.0 to 35.0 parts by mass.
[0079] Therefore, it is preferable that, per 100 parts by mass of the (E) component, the content of the (E-1) component is 5.0 to 30.0 parts by mass, the content of the (E-2) component is 10.0 to 28.0 parts by mass, the content of the (E-3) component is 15.0 to 40.0 parts by mass, and the content of the (E-4) component is 5.0 to 40.0 parts by mass.
[0080] From the viewpoints of ejection properties and curing characteristics, the content of the (A) component is preferably 55.0 to 95.0 parts by mass, more preferably 60.0 to 90.0 parts by mass, and particularly preferably 65.0 to 85.0 parts by mass, per 100 parts by mass of the combined total of the (A), (B), (C), (D), and (F) components.
[0081] The content of component (B) is not particularly limited as long as it is an amount that allows a network structure to be formed in the cured product of the thermally conductive silicone composition. The amount is preferably such that the ratio (H / Vi) of the number of hydrogen atoms bonded to silicon atoms in component (B) to the number of alkenyl groups in component (A) Vi is 0.1 or more and less than 3.5, more preferably 0.2 to 2.5, and particularly preferably 0.3 to 2.0.
[0082] The content of component (C) is a catalytic amount relative to the total amount of the thermally conductive silicone composition. Specifically, from the viewpoint of curability, the content of component (C) is preferably 0.1 to 1,000 ppm by weight, and particularly preferably 0.5 to 200 ppm by weight, calculated as platinum metal atoms, relative to 100 parts by weight of components (A), (B), (C), (D), and (F) combined.
[0083] There are no particular limitations on the amount of component (F) contained, so long as it does not impair the intended use of the thermally conductive silicone composition.
[0084] (Method of producing thermally conductive silicone composition) The thermally conductive silicone composition can be produced by uniformly kneading the essential components (A) through (E) and the optional component (F) using a mixing means such as a universal kneader or kneader.
[0085] (cured product) A cured product obtained by curing the thermally conductive silicone composition can be obtained by curing the thermally conductive silicone composition. The curing conditions (i.e., heating temperature and heating time) can be appropriately adjusted according to the heat resistance temperature of the member to which the thermally conductive silicone composition is applied. From the viewpoint of the heat resistance and operability of the member, the heating temperature is preferably 20 to 150°C, and more preferably more than 23°C and 100°C or less. The heating time depends on the amount of material to be cured and the heating output of the curing equipment, but from the viewpoint of the simplicity of the curing process, it is preferably 15 minutes to 3 hours, and more preferably 30 minutes to 2 hours.
[0086] (Application) The cured product obtained by curing the thermally conductive silicone composition can be used as a heat dissipation component for electronic devices, integrated circuit elements, and other electronic components. Thus, electronic components containing the thermally conductive silicone composition are also within the scope of the present invention. EXAMPLES
[0087] The present invention will be described in more detail below with reference to examples and comparative examples. In these examples, the parts indicate parts by mass, and the viscosity indicates the viscosity at 23° C. The present invention is not limited to these examples.
[0088] (Ingredients used) The components used in the examples and comparative examples are as follows. (A) Polyorganosiloxane having an alkenyl group bonded to a silicon atom (A-1): Both-end vinyldimethylpolysiloxane: M vi D n M vi and a linear vinyldimethylpolysiloxane with a viscosity of 0.5 Pa s. (A-2): One-terminated vinyldimethylpolysiloxane: M vi D n A linear vinyldimethylpolysiloxane designated M and having a viscosity of 0.03 Pa·s.
[0089] (B) Polyorganohydrogensiloxane having hydrogen atoms bonded to silicon atoms (B-1): Single-terminated hydrogen polysiloxane: M H D n Linear polymethylhydrogensiloxane (effective hydrogen content 0.04 mmol / g, viscosity 0.02 mPa s), indicated by M (B-2): Both-end hydrogen polysiloxane: M H D n M H Linear polymethylhydrogensiloxane (effective hydrogen content 1.2 mmol / g, viscosity 10 mPa s) (B-3): Hydrogen polysiloxane with side chains at both ends: Both ends are MH The intermediate units are D and D. H Linear polymethylhydrogensiloxane (effective hydrogen content 2.6 mmol / g, viscosity 20 mPa s) consisting of only units
[0090] (C) Platinum catalyst (C-1): Karlstedt catalyst (platinum (0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex, 2.0% by mass in terms of platinum atom)
[0091] (D) Siloxane Compound (D-1): [ka] A mixture of cyclic siloxane compounds (n=10-50)
[0092] (E) Thermally conductive filler Since the thermally conductive fillers used in the examples are monodisperse, the peak diameter of the particle size distribution of the thermally conductive fillers used in the examples is synonymous with the "average particle diameter." Also, the "particle diameter" in the table refers to the "peak diameter of the particle size distribution." (E-1) Silicon carbide having a particle size distribution peak in the range of 10 μm to 40 μm (E-1-1): Silicon carbide (having a particle size distribution peak at 20 μm, thermal conductivity 200 W / mK, BET specific surface area 0.2 m 2 / g, Supplier: Shinano Electric Smelting Co., Ltd. (E-1-2): Silicon carbide (having a particle size distribution peak at 25 μm, thermal conductivity 200 W / mK, BET specific surface area 0.1 m 2 / g, Supplier: Shinano Electric Smelting Co., Ltd. (E-1-3): Silicon carbide (having a particle size distribution peak at 30 μm, thermal conductivity 200 W / mK, BET specific surface area 0.1 m 2 / g, Supplier: Shinano Electric Smelting Co., Ltd. (E-2): First thermally conductive filler (E-2-1): Zinc oxide (having a particle size distribution peak at 0.1 μm, thermal conductivity 25 W / mK, BET specific surface area 9.0 m 2 / g, Supplier: Zochem LLC) (E-2-2): Aluminum nitride (having a particle size distribution peak at 0.1 μm, thermal conductivity 180 W / mK, BET specific surface area 2.8 m 2 / g, Supplier: Tokuyama Corporation) (E-2-3): Alumina (having a particle size distribution peak at 0.5 μm, thermal conductivity 30 W / mK, BET specific surface area 4.6 m 2 / g, Supplier: Sumitomo Chemical Co., Ltd. (E-2-4): Silicon carbide (having a particle size distribution peak at 0.5 μm, thermal conductivity 200 W / mK, BET specific surface area 5.0 m 2 / g, Supplier: Shinano Electric Refining Co., Ltd. (E-2-5): Alumina (having a particle size distribution peak at 0.3 μm, thermal conductivity 30 W / mK, BET specific surface area 7.2 m 2 / g, Supplier: Sumitomo Chemical Co., Ltd. (E-2-6): Alumina (having a particle size distribution peak at 0.8 μm, thermal conductivity 30 W / mK, BET specific surface area 2.1 m 2 / g, Supplier: Sumitomo Chemical Co., Ltd. (E-3): Second thermally conductive filler (E-3-1): Alumina (having a particle size distribution peak at 3.0 μm, thermal conductivity 30 W / mK, BET specific surface area 0.6 m 2 / g, Supplier: Sumitomo Chemical Co., Ltd. (E-3-2): Alumina (having a particle size distribution peak at 5.0 μm, thermal conductivity 30 W / mK, BET specific surface area 0.3 m 2 / g, Supplier: Sumitomo Chemical Co., Ltd. (E-3-3): Silicon carbide (having a particle size distribution peak at 5.0 μm, thermal conductivity 200 W / mK, BET specific surface area 1.5 m 2 / g, Supplier: Shinano Electric Refining Co., Ltd. (E-3-4): Alumina (having a particle size distribution peak at 2.0 μm, thermal conductivity 30 W / mK, BET specific surface area 1.0 m 2 / g, Supplier: Sumitomo Chemical Co., Ltd. (E-3-5): Alumina (having a particle size distribution peak at 7.0 μm, thermal conductivity 30 W / mK, BET specific surface area 0.4 m 2 / g, Supplier: Sumitomo Chemical Co., Ltd. (E-4): Third thermal conductive filler (E-4-1): Aluminum nitride (having a particle size distribution peak at 25 μm, thermal conductivity 180 W / mK, BET specific surface area 0.2 m 2 / g, Supplier: Toyo Aluminum Co., Ltd. (E-5): Other thermally conductive fillers (E-5-1): Silicon carbide (having a particle size distribution peak at 60 μm, thermal conductivity 200 W / mK, BET specific surface area 0.2 m 2 / g, Supplier: Shinano Electric Refining Co., Ltd. (E-5-2): Alumina (having a particle size distribution peak at 25 μm, thermal conductivity 30 W / mK, BET specific surface area 0.1 m 2 / g, Supplier: Sumitomo Chemical Co., Ltd. (E-5-3): Aluminum nitride (having a particle size distribution peak at 60 μm, thermal conductivity 180 W / mK, BET specific surface area 0.1 m 2 / g, Supplier: Toyo Aluminum Co., Ltd.
[0093] (F) Other Ingredients (F-1) Reaction inhibitor Dimethylbis(1,1-dimethyl-2-propynyloxy)silane (supplied by Momentive Performance Materials Japan, LLC)
[0094] (1) Preparation of Base Polymer (1) (Silicone Composition 1 Excluding Filler) The base polymers to be compounded in the examples and comparative examples were kneaded in the compositions shown in Table 1 using a planetary mixer to prepare base polymer (1).
[0095] (2) Preparation of Base Polymer (2) (Silicone Composition 2 Excluding Filler) Base polymer (2) was prepared according to the composition shown in Table 2 in the same manner as base polymer (1).
[0096] (3) Preparation of Thermally Conductive Silicone Composition Examples 1 to 20, Comparative Examples 1 to 13 Thermally conductive fillers and base polymers of each component were blended according to the compositions shown in Tables 3 to 13, and kneaded using a planetary mixer to prepare thermally conductive silicone compositions.
[0097] (Evaluation method) 1. Thermal Conductivity Using a thermal conductivity meter (TPS 1500) (Kyoto Electronics Manufacturing), a plastic container with an inner diameter of 30 mm and a depth of 10 mm was filled with the composition and left at 70°C for 1 hour to harden the composition, producing a sample. The thermal conductivity was measured by sandwiching the sensor of the thermal conductivity meter between two of the obtained samples. The heat dissipation was judged according to the following criteria. A thermal conductivity of 7.0 W / (m K) or more was considered to have excellent heat dissipation.
[0098] 2. Flow rate (dischargeability) The flow rate (g / min) of the composition was measured as follows and used to evaluate the dischargeability. (1) The composition was filled into a 30 cc EFD syringe manufactured by Nordson Corporation. (2) A high-precision dispenser with compensation function, SuperΣxIII, manufactured by Musashi Engineering Co., Ltd., was used as the dispenser, and the composition was dispensed at 0.625 MPa for 1 minute. (3) The amount of the composition discharged was measured, and the flow rate (g / min) of the composition was calculated. A flow rate of 20 g / min or more was determined to be excellent in dischargeability.
[0099] 3. BLT The BLT, i.e., the bond line thickness of the heat dissipation material, was measured as follows. Two 10 mm x 10 mm silicon chips were prepared, and the thickness was measured in advance. After the thickness measurement, 0.01 ml of the composition was applied to the silicon chips, which were then sandwiched between the silicon chips and subjected to a load of 100 N, and then the chips were left at 70°C for 1 hour. The thickness was measured using a micrometer. The thickness of the BLT was calculated by subtracting the thickness of two silicon chips from the thickness after the thickness measurement. A composition was judged to have a low BLT if the BLT was 60 μm or less.
[0100] 4.Breakdown voltage The dielectric breakdown voltage was measured according to JIS K 6249. The dielectric breakdown voltage was measured using an electrical insulating oil breakdown voltage tester Porta Test A-2 (manufactured by Soken Denki Co., Ltd.). The composition was cured at 70°C for 1 hour, and a voltage of 2 kV / sec was applied to a test piece adjusted to a thickness of 1 mm. The voltage at which the test piece became conductive and lost its electrical insulation was taken as the dielectric breakdown voltage. When the dielectric breakdown voltage was 1.0 kV / mm or more, the composition was judged to have excellent electrical insulation.
[0101] 5.Volume resistivity The volume resistivity was measured in accordance with JIS K 6249. Specifically, the volume resistivity was measured using an Advantest R8340 digital ultra-high resistance / microcurrent meter (Advantest Corporation). The composition was cured at 70°C for 1 hour, and a test piece adjusted to a thickness of 1 mm was applied with a voltage of 500 V, and the volume resistivity was calculated from the current value obtained as the response value. When the volume resistivity was 1.00×10 12 When the electrical insulation property of the composition was Ω·cm or more, the composition was judged to have excellent electrical insulation property.
[0102] [Table 1]
[0103] [Table 2]
[0104]
Table 3
[0105]
Table 4
[0106]
Table 5
[0107]
Table 6
[0108]
Table 7
[0109]
Table 8
[0110]
Table 9
[0111]
Table 10
[0112]
Table 11
[0113]
Table 12
[0114] [Table 13]
[0115] As is clear from the table, the thermally conductive silicone compositions of the Examples had low BLT and were excellent in electrical insulation, dischargeability, and heat dissipation. In other words, by setting the content of component (E) relative to the total content of components (A) to (D), and the content of component (E-2) relative to the content of component (E), within a specified range, it was possible to adjust the thermal conductivity and dischargeability while maintaining the BLT properties. In particular, when comparing Example 1 and Example 10, when the amount of "silicone composition excluding filler" was large (i.e., when the total content of components (A) to (D) was 6.0 parts by mass or more per 100 parts by mass of component (E)), the BLT was lower and the ejection properties and heat dissipation properties were superior. Comparing Examples 1 to 3, when the amount of component (E-1) was large, the heat dissipation properties were more excellent. Comparing Examples 1 and 2, when the amount of the (E-1) component was small, the electrical insulation was superior. Furthermore, compared to Example 3, Examples 1 and 2 had a lower BLT and were superior in ejection properties. Comparing Examples 1, 4, and 7, when the particle size of the (E-1) component was large, the thermal conductivity was superior. Among Examples 1 to 9, Examples 1, 4, and 7 had lower BLT and superior dischargeability.
[0116] The composition of Comparative Example 1 did not contain the component (E-4). Therefore, the composition of Comparative Example 1 was inferior to the compositions of Examples 1 to 3 in terms of ejection properties and electrical insulation properties. The composition of Comparative Example 2 does not contain the component (E-4). The composition of Comparative Example 2 contains a thermally conductive filler having a larger peak in the particle size distribution than the component (E-4). Therefore, the composition of Comparative Example 2 was inferior to the composition of Example 1 in terms of dischargeability. The relationship between Examples 4 to 6 and Comparative Example 3, and the relationship between Examples 7 to 9 and Comparative Example 5 are similar to the relationship between Examples 1 to 3 and Comparative Example 1. Moreover, the relationship between Examples 4 and Comparative Example 4, and the relationship between Example 7 and Comparative Example 6 are similar to the relationship between Example 1 and Comparative Example 2. The composition of Comparative Example 7 did not contain the components (E-1) and (E-4), and therefore the composition of Comparative Example 7 did not come together as a composition. The composition of Comparative Example 8 does not contain the (E-1) component and the (E-4) component. The composition of Comparative Example 4 contains silicon carbide having a larger peak in the particle size distribution than the (E-1) component. Therefore, the composition of Comparative Example 8 was inferior to the composition of Example 1 in terms of ejection property and electrical insulation property. The composition of Comparative Example 9 contained a thermally conductive filler having a lower thermal conductivity than the component (E-4), and therefore the composition of Comparative Example 9 had poor thermal conductivity. The composition of Comparative Example 10 did not contain the component (E-4). Therefore, the composition of Comparative Example 10 was inferior to the composition of Example 10 in terms of ejection properties and electrical insulation properties. The composition of Comparative Example 11 did not contain the component (E-4). Therefore, the composition of Comparative Example 11 was inferior to the composition of Example 11 in ejection properties and electrical insulation properties. In the compositions of Comparative Examples 12 and 13, the content of the component (E-2) exceeds 28.0 parts by mass per 100 parts by mass of the thermally conductive filler, and therefore the compositions of Comparative Examples 12 and 13 could not be combined into a single composition.
Claims
1. (A) a polyorganosiloxane having an alkenyl group bonded to a silicon atom; (B) a polyorganohydrogensiloxane having a hydrogen atom bonded to a silicon atom; (C) platinum-based catalyst; (D) a compound represented by the following general formula (1): 【Chemistry 11】 [During the ceremony, R 1 : a group having an alkoxysilyl group having 1 to 4 carbon atoms R 2 The following general formula (2): 【Chemistry 12】 (In the formula, R 4 are each independently a monovalent hydrocarbon group having 1 to 12 carbon atoms, and Y is R 4 and aliphatic unsaturated groups, and d is an integer of 2 to 60. X: each independently a divalent hydrocarbon group having 2 to 10 carbon atoms a and b: each independently an integer of 1 or more c: an integer of 0 or more a+b+c: an integer of 4 or more R 3 each independently represents a monovalent hydrocarbon group having 1 to 6 carbon atoms or a hydrogen atom. A siloxane compound represented by the formula: (E) a thermally conductive filler; A thermally conductive silicone composition comprising: The component (A) contains (A-1) a polyorganosiloxane having two or more alkenyl groups bonded to silicon atoms in the molecule, The component (B) contains (B-1) a polyorganohydrogensiloxane having two or more hydrogen atoms bonded to silicon atoms in the molecule, The component (E) is (E-1) Silicon carbide having a particle size distribution peak in the range of 10 μm to 40 μm; (E-2) a first thermally conductive filler having a thermal conductivity of 10 W / mK to 300 W / mK and a particle size distribution peak in the range of 0.1 μm to 1.0 μm; (E-3) A second thermally conductive filler having a thermal conductivity of 10 W / mK to 300 W / mK and a particle size distribution peak in the range of more than 1.0 μm and less than 10 μm; and (E-4) A third thermally conductive filler (excluding silicon carbide) having a thermal conductivity of 60 W / mK to 300 W / mK and a particle size distribution peak in the range of 10 μm to 40 μm; The total content of components (A), (B), and (C) is 1.0 to 10.0 parts by mass per 100 parts by mass of component (E); and A thermally conductive silicone composition, in which the amount of component (E-2) is 28.0 parts by mass or less per 100 parts by mass of component (E).
2. The component (E-2) is at least one selected from the group consisting of alumina, aluminum nitride, aluminum hydroxide, magnesium oxide, zinc oxide, crystalline silica, aluminum, boron nitride, and graphitized carbon; The component (E-3) is at least one selected from the group consisting of alumina, aluminum nitride, aluminum hydroxide, magnesium oxide, zinc oxide, crystalline silica, aluminum, boron nitride, and graphitized carbon; and 2. The thermally conductive silicone composition according to claim 1, wherein component (E-4) is at least one member selected from the group consisting of aluminum nitride, boron nitride, and graphitized carbon.
3. The thermally conductive silicone composition according to claim 1, further comprising at least one member selected from the group consisting of (A-2) a polyorganosiloxane having one alkenyl group bonded to a silicon atom in the molecule, and (B-2) a polyorganohydrogensiloxane having one hydrogen atom bonded to a silicon atom in the molecule.
4. The thermally conductive silicone composition according to claim 2, further comprising at least one member selected from the group consisting of (A-2) a polyorganosiloxane having one alkenyl group bonded to a silicon atom in the molecule, and (B-2) a polyorganohydrogensiloxane having one hydrogen atom bonded to a silicon atom in the molecule.
5. Relative to 100 parts by mass of component (E), The content of the component (E-1) is 5.0 to 30.0 parts by mass, The content of the component (E-2) is 10.0 to 28.0 parts by mass, The content of the component (E-3) is 15.0 to 40.0 parts by mass, and The content of the component (E-4) is 5.0 to 40.0 parts by mass. The thermally conductive silicone composition according to claim 1 .
6. Relative to 100 parts by mass of component (E), The content of the component (E-1) is 5.0 to 30.0 parts by mass, The content of the component (E-2) is 10.0 to 28.0 parts by mass, The content of the component (E-3) is 15.0 to 40.0 parts by mass, and The content of the component (E-4) is 5.0 to 40.0 parts by mass. The thermally conductive silicone composition according to claim 2.
7. Relative to 100 parts by mass of component (E), The content of the component (E-1) is 5.0 to 30.0 parts by mass, The content of the component (E-2) is 10.0 to 28.0 parts by mass, The content of the component (E-3) is 15.0 to 40.0 parts by mass, and The content of the component (E-4) is 5.0 to 40.0 parts by mass. The thermally conductive silicone composition according to claim 3.
8. Relative to 100 parts by mass of component (E), The content of the component (E-1) is 5.0 to 30.0 parts by mass, The content of the component (E-2) is 10.0 to 28.0 parts by mass, The content of the component (E-3) is 15.0 to 40.0 parts by mass, and The content of the component (E-4) is 5.0 to 40.0 parts by mass. The thermally conductive silicone composition according to claim 4.
9. A cured product obtained by curing the thermally conductive silicone composition according to any one of claims 1 to 8.
10. An electronic part comprising the thermally conductive silicone composition according to any one of claims 1 to 8.
Citation Information
Patent Citations
Silicone gel composition and silicone gel
JP2001214063A
Heat conductive silicone composition
JP2006143978A
Thin bond line silicone adhesive composition and method for producing same
JP2007503506A
High thermal conductivity silicone rubber composition for fixing roll or belt for office machine, and fixing roll and fixing belt
JP2011107553A
Ultraviolet-curable silicone adhesive composition and method for producing laminate
JP2020055945A